Ke Arah Pematuhan Halal Menerusi Penubuhan Jawatankuasa Pengawasan Syariah Di Hospital - Muhammad Adib Samsudin; Mohd Izhar Ariff Mohd Kashim; Mohammad Zaini Yahaya; Ahmad Munawar Ismail; Rozida Mohd Khalid; Wan Kamal Wan Mujani; Hayatullah Laluldin; Syed Azhar Syed Sulaiman; Irwan Mohd Subri (Institut Sosial Malaysia (ISM), 2024)
Volume : 11